2012
DOI: 10.1007/s11418-012-0722-3
|View full text |Cite
|
Sign up to set email alerts
|

The phytoalexin camalexin mediates cytotoxicity towards aggressive prostate cancer cells via reactive oxygen species

Abstract: Camalexin is a phytoalexin that accumulates in various cruciferous plants upon exposure to environmental stress and plant pathogens. Besides moderate antibacterial and antifungal activity, camalexin was reported to also exhibit antiproliferative and cancer chemopreventive effects in breast cancer and leukemia. We studied the cytotoxic effects of camalexin treatment on prostate cancer cell lines and whether this was mediated by reactive oxygen species (ROS) generation. As models, we utilized LNCaP and its aggre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…Our laboratory has shown that camalexin induced apoptosis in prostate cancer cells (PCa) through the generation of Reactive Oxygen Species (ROS), and that the more aggressive prostate cancer cells with higher levels of endogenous ROS displayed greater sensitivity to camalexin treatments evidenced by decreased viability and increased apoptosis as compared to the less aggressive prostate cancer cells, while normal epithelial cells were unaffected [ 9 ]. The generation of intracellular ROS activates several signal transduction pathways leading to inflammation, cell cycle progression, apoptosis, migration, and invasion in cancer [ 10 ]. Thus, excessive production of ROS or inadequacy in a cell’s antioxidant defense system (or both) induces oxidative stress with consequent initiation of cellular processes associated with initiation and development of many cancers including prostate cancer [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our laboratory has shown that camalexin induced apoptosis in prostate cancer cells (PCa) through the generation of Reactive Oxygen Species (ROS), and that the more aggressive prostate cancer cells with higher levels of endogenous ROS displayed greater sensitivity to camalexin treatments evidenced by decreased viability and increased apoptosis as compared to the less aggressive prostate cancer cells, while normal epithelial cells were unaffected [ 9 ]. The generation of intracellular ROS activates several signal transduction pathways leading to inflammation, cell cycle progression, apoptosis, migration, and invasion in cancer [ 10 ]. Thus, excessive production of ROS or inadequacy in a cell’s antioxidant defense system (or both) induces oxidative stress with consequent initiation of cellular processes associated with initiation and development of many cancers including prostate cancer [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple agents such as artesunate, NPI-0052, and plumbagin showed toxicity against leukemia cells which are relied on its ability to generate ROS [ 24 – 26 ]. According to previous studies, camalexin could induce ROS in prostate cancer and leukemia cells [ 6 , 7 ]. Interestingly, camalexin was found unable to induce ROS in erythrocytes in a recent study [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Camalexin has been extensively studied for its role in plant chemical defense mechanisms and has been shown to exert cytotoxic against human protozoan pathogen, Trypanosoma cruzi [ 5 ]. Camalexin also exhibits antitumor effects against prostate cancer and leukemia cells [ 6 , 7 ]. However, the underling mechanisms of the antitumor activities of camalexin are still elusive.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to bacterial pathways, some eukaryotic pathways were also reconstituted in vitro . The biosynthetic pathways of dhurrin, which plays an important role in plant defense against pathogens [35] , and camalexin, which is cytotoxic against aggressive prostate cancer cell lines [36] , have been studied in cell-free synthetic enzyme system. Kahn and colleagues reconstituted the entire dhurrin biosynthetic pathway in vitro using enzymes from the natural host organism [37] .…”
Section: Cell-free Synthetic Enzyme Engineeringmentioning
confidence: 99%